1984
DOI: 10.1080/15287398409530625
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat and nitrofurantoin inhibit growth ofescherichia coliby inducing stringency

Abstract: The herbicide paraquat and the antibiotic nitrofurantoin (redox-active compounds that can transfer electrons singly to oxygen) induced intracellular accumulation of the regulatory inhibitor guanosine tetraphosphate (stringency) in Escherichia coli. This mechanism is sufficient to account for the rapid bacteristasis produced in minimal medium by these agents. The growth inhibition and stringency induction were prevented by inclusion of specific amino acids in the medium. Stringency was first reported to result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Seither and Brown (46) reported that growth inhibition of E. coli by paraquat, a herbicide, and nitrofurantoin, an antibiotic, was induced by the stringent response. Both compounds are believed to block biosynthetic pathways of specific amino acids and cause amino acid starvation in the cells.…”
Section: Resultsmentioning
confidence: 99%
“…Seither and Brown (46) reported that growth inhibition of E. coli by paraquat, a herbicide, and nitrofurantoin, an antibiotic, was induced by the stringent response. Both compounds are believed to block biosynthetic pathways of specific amino acids and cause amino acid starvation in the cells.…”
Section: Resultsmentioning
confidence: 99%
“…The stringency response is defined as intracellular accumulation of guanosine 5'-diphosphate 3'-diphosphate, which is a regulatory inhibitor of biosynthetic processes in bacteria (25). Nitrofurantoin blocks synthesis of branchedchain amino acids such as valine and leucine (26). The observed decrease in the MIC of nitrofurantoin for a clinical bacterial isolate (E. coli serotype 018) during hyperoxic exposure may be due to a combination of these mechanisms.…”
Section: Discussionmentioning
confidence: 97%
“…This oxygen-derived free radical may undergo further reduction to form H202, which is toxic for bacteria. Hydrogen peroxide may take part in the Fenton reaction, where it is converted to the highly reactive hydroxyl radical (16 (25,26). The stringency response is defined as intracellular accumulation of guanosine 5'-diphosphate 3'-diphosphate, which is a regulatory inhibitor of biosynthetic processes in bacteria (25).…”
Section: Discussionmentioning
confidence: 99%
“…SB 205952 therefore appears to have a second mechanism of action which induces stringency but which is independent of IRS inhibition. Nitrofurantoin and related compounds (27,38) are among the agents known to invoke ppGpp accumulation and stringency, and oxidative inactivation of dihydroxyacid dehydratase has been implicated (38). This enzyme is a key component of the isoleucine biosynthetic pathway in which it functions to convert ␣,␤-dihydroxy-␤-methylvalerate to ␣-keto-␤-methylvalerate (41).…”
Section: Discussionmentioning
confidence: 99%